Eyebrow Cream Preparation Formulation Based on Activated Carbon from Elaeis guineensis Jacq. Shells - Annisaa Siti Zulaicha; Deviana Safitri; Iwan Syahjoko Saputra; Wahyu Solafide Sipahutar; Yunita Fahni (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2026)
This study aims to utilize palm kernel shell waste as a source of activated carbon for the formulation of safe and sustainable eyebrow cream. Activated carbon was obtained through pyrolysis and physical activation at 800°C, then characterized using proximate analysis, SEM-EDX, XRD, and FTIR to determine its structure, composition, and purity. The characterization results showed that the activated carbon had 100% carbon purity, a porous amorphous structure, and a predominance of C=C groups, indicating a non-polar surface with high adsorptive potential. The activated carbon was then formulated into four variations of eyebrow cream using the hot emulsification method and evaluated through organoleptic, homogeneity, pH, and smudge resistance tests. All formulas showed physical stability for four weeks, a semi-solid texture, homogeneity without granules, and increased color with increasing activated carbon concentration. The pH value of all formulas was 5, within the safe range for skin. This study shows that palm kernel shell activated carbon not only meets the characteristics of stable and safe cosmetic pigments but also provides a natural coloring alternative that supports the concepts of clean beauty, green cosmetics, and the circular economy. Thus, palm kernel shell waste activated carbon has great potential to be developed as an active ingredient in decorative cosmetics, particularly natural-based eyebrow creams.